Antiacne and Anti-Inflammatory Effects of Phenolic Compounds from Quercus acutissima Carruth. Leaves. (31st December 2022) - Kim, Eun Bin; Lee, Eun Kyung; Son, Se Yeon; Lee, Min Won
Abstract : Quercus plants are widely distributed in Korea and have been used for their antiallergic and anti-inflammatory properties to treat dermatitis. The phenolic compounds of Quercus acutissima Carruth (QA) are estimated to have antioxidant and anti-inflammatory activities, based on the results of previous studies with Quercus mongilica, Quercus stenophylla, Quercus gilva Blame., and Quercus acuta Thunb. We yield QA extract and the isolated phenolic compounds (hyperoside (1 ), astragalin (2 ), kaempferol 3–O-(6″- galloyl)– β –D–glucopyranoside (KGG) (3 ), quercetin 3–O-(6″-O-galloyl)- β –D–glucopyranoside (QGG) (4 ), pedunculagin (5 ), and casuarinin (6 )) and were identified using NMR. Among them, KGG (3 ) and QGG (4 ) were isolated for the first time from QA. QA extract and the isolated phenolic compounds demonstrated antioxidative, anti-inflammatory, and antiacne activities in RAW 264.7 mouse macrophage cells in vitro. 3 –6 demonstrated strong inhibitory activities in the DPPH scavenging and NO production assay and anti-inflammatory and antiacne activities through western blotting (NLRP3, IL-1 β, and 5 α -reductase). The most outstanding activity in all experiments was casuarinin (6 ). The study findings suggest potential therapeutic candidates for acne.